2006
DOI: 10.1212/01.wnl.0000196641.05913.27
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate causes toxic neuropathy in MELAS

Abstract: DCA at 25 mg/kg/day is associated with peripheral nerve toxicity resulting in a high rate of medication discontinuation and early study termination. Under these experimental conditions, the authors were unable to detect any beneficial effect. The findings show that DCA-associated neuropathy overshadows the assessment of any potential benefit in MELAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
239
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(251 citation statements)
references
References 25 publications
2
239
1
6
Order By: Relevance
“…It was suggested that DCA could rapidly translate to cancer clinical trials because it has been used to treat lactic acidosis and found to be relatively safe in humans (43,44). However, the doses of DCA required to induce apoptosis in cancer cells are very high and unlikely to be achieved clinically without causing significant side effects (45). When combined with 5-FU, low doses of DCA and 5-FU could significantly induce apoptosis in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that DCA could rapidly translate to cancer clinical trials because it has been used to treat lactic acidosis and found to be relatively safe in humans (43,44). However, the doses of DCA required to induce apoptosis in cancer cells are very high and unlikely to be achieved clinically without causing significant side effects (45). When combined with 5-FU, low doses of DCA and 5-FU could significantly induce apoptosis in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the first, a blinded placebo-controlled study was performed with oral DCA administered at 25 mg kg À1 day À1 in 30 patients with MELAS syndrome (mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes) (Kaufmann et al, 2006). Most patients enrolled in the DCA arm developed symptomatic peripheral neuropathy, compared with 4 out of 15 in the placebo arm, leading to the termination of the study.…”
Section: Dca: Mechanism Of Action and Clinical Experiencementioning
confidence: 99%
“…Therefore, a third trial was organized at Columbia University, which was specific for MELAS [10]. This also was a phase III double-blind, randomized, placebocontrolled trial (Table 1).…”
Section: Introductionmentioning
confidence: 99%